The Influence of POGIL and MFI Models on Science Literacy and Science Process Skills for Junior High School - Sirry Alvina; Mellyzar Mellyzar; Syarifah Rita Zahara; Masrina Masrina; Sella Afrianti (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine how the influence of the POGIL model on the ability of the science process and scientific literacy of students, in addition to knowing how the MFI model affects science process skills and scientific literacy of students and the comparison of POGIL and MFI models on science process skills and scientific literacy of Lhokseumawe City Junior High School students. This research uses an approach to quantitative research. The population of this research is the seventh-grade students of SMP in Lhokseumawe city. The research sample taken is SMPN students Arun, SMPN 1 Lhokseumawe, and SMPN 2 Lhokseumawe every 3 schools that consist of 2 experimental classes (POGIL and MFI models) and 1 control class (conventional) with a total of 9 classes. The research instrument used is a test question for knowing students' literacy skills, practicum guide sheets, and observation sheets to determine students' science process skills. In the class with the POGIL model, the average value of scientific literacy ability is 32.27, and science process skills are 81.32. In class with the MFI model, the average value of science literacy skills is 26.84, and process skills science 88.71. While the control class has an average value of scientific literacy ability of 12.77 and science process skills of 68.54. Based on Test Test output Statistics data of students' scientific literacy and science process skills are known as the value of asymp. Sig. (2-tailed) of 0.00 < 0.05, it can be concluded that the POGIL model has a significant effect on students' scientific literacy and science process skills.  The results for the MFI class scores of students' scientific literacy skills and science process skills, because of the Asymp value. Sig. (0.000) < (0.05) so that learning with the MFI model affects the scientific literacy ability and science process skills of students. Classes taught with POGIL and MFI models with Asymp grades. Sig. (0.099 > (0.05) means that there is no significant difference in students' scientific literacy skills between students who are taught with the POGIL model and students who are taught with the MFI model but there is a significant difference in science process skills of students with POGIL and MFI models, where the MFI model students' science process skills higher than the POGIL model